(untitled) (Environmental Smoke, 2024)
In this study we report a new occurrence of Paragonimus Braun, 1899 in the Amazon province, recovered from a new host, the semi-terrestrial sesarmid crab Armases benedicti (Rathbun, 1897). Additionally, we would like to alert the health authorities to the presence of trematodes in the urban area of Belém-PA. The specimens of A. benedicti were manually collected on the banks of the Guamá River (01°28’22.6”S; 048°26’49.79”W) in January 2024. We accounted for 42 specimens of A. benedicti, with one male showing the presence of an excysted metacercariae of Paragonimus sp. in the seminal tube. Despite the low number of individuals, the occurrence of this parasite in the region raises the possible parasitism in other organisms such as mollusks, other crustaceans and fish, which are directly consumed by humans. Thus, this paper focuses in warning the risk of contamination of the population, especially by pulmonary paragonimiasis, however, further studies and new samples are needed to identify this parasite in species level and describe its life cycle in the region.